Long non‐coding RNA SNHG16 decreased SMAD4 to induce gemcitabine resistance in pancreatic cancer via EZH2‐mediated epigenetic modification - Yi Yu; Yu‐Feng Zou; Run‐Qi Hong; Wen‐Jie Chen; Liang Chen; Wen‐Qi Chen; Hui‐Peng Wang; Yuan Yu (Kaohsiung Journal of Medical Sciences, 2022)
Abstract Gemcitabine resistance (GR) in pancreatic cancer (PC) results in poor patient outcomes. SMAD family member (Smad4) dysregulation is a significant role of GR in PC, and EZH2 is involved in Smad4 expression in tumor progression. Interestingly, lncRNA small nucleolar RNA host gene 16 (SNHG16) might interact with EZH2, indicating a potential pathway to overcome gemcitabine‐resistant PC progression. We investigated the role of the SNHG16/EZH2/Smad4 pathway in gemcitabine‐resistant PC cells (PANC‐1/GR and SW1990/GR). First, we found that SNHG16 was upregulated both in wild‐type PC cells and in gemcitabine‐resistant PC cells. SNHG16 overexpression reduced gemcitabine cytotoxicity and apoptosis in PC cells. Meanwhile, SNHG16 upregulation caused p‐Akt elevation and Smad4 reduction. However, SNHG16 silencing induced the opposite trend. Then, we found that EZH2 was enriched in SNHG16 based on RIP and RNA pulldown. In particular, SNHG16 overexpression promoted the interaction between EZH2 and the Smad4 promoter according to Chromatin immunoprecipitation‐quantitative polymerase chain reaction. Finally, both EZH2 inhibition and Smad4 upregulation increased gemcitabine cytotoxicity and apoptosis in PC cells during SNHG16 overexpression. Moreover, both treatments decreased p‐Akt and increased Smad4. Collectively, lncRNA SNHG16 decreased Smad4 to induce GR in PC via EZH2‐mediated epigenetic modification.